309 Tumor Necrosis Factor-Inducible Gene 6 Protein: A Novel Neuroprotective Factor Against Inflammatory Developmental Brain Injury. (October 2012) - Bertling, F; Prager, S; Hermann, R; Bendix, I; Wisniewski, HG; FelderhoffMüser, U; Keller, M
Abstract : Background and Aims: An important factor of developmental brain injury is inflammation. It has been shown that tumor necrosis factor-inducible gene 6 protein (TSG-6) has anti-inflammatory effects in several inflammatory conditions. Nothing is known so far about the role of TSG-6 in the developing brain, its impact on inflammation and its therapeutic potential. Methods: PCR, Western Blotting and Immunohistochemistry was performed according to standard protocols. Brain hemispheres of untreated Wistar rats (p1-p15) were evaluated under developmental aspects of TSG-6. LPS-treated rats (0.25mg/kg LPS i.p. on p3) were evaluated under pathological aspects of TSG-6. To evaluate whether exogenous rhTSG-6 reduces inflammatory-induced brain injury, newborn Wistar rats, exposed to LPS at p3, were treated with rhTSG-6 i.p. (four repetitive doses of 2.25mg/kg every 12h, first dose three hours before LPS-injection). Results: Investigations of TSG-6's developmental brain expression showed a linear increase from p1 to p15 on gene level. Additionally, different expression was detected in Cortex, Thalamus and Striatum on gene level at p6. Expression of TSG-6 after LPS treatment (0–24h) was significantly increased on gene level and tendentiously on protein level. cCaspase-3, a marker of apoptosis, showed a significant down-regulation of >30% under additional TSG-6 treatment versus sole LPS exposure (n=12–14, p=0, 025). Conclusions: TSG-6 Expression is developmentally regulated and increased after LPS exposure. The reduction of activated Caspase-3 demonstrates the neuroprotective potential of exogenous TSG-6 administration in inflammatory-induced developmental brain injury.